2021
DOI: 10.3390/ijerph18168820
|View full text |Cite
|
Sign up to set email alerts
|

Research on Adolescents Regarding the Indirect Effect of Depression, Anxiety, and Stress between TikTok Use Disorder and Memory Loss

Abstract: This research involved the participation of 3036 Chinese students in the first and second years of senior high school. The adolescents were active users of TikTok. The mediating effect of depression, anxiety, and stress between TikTok use disorder and memory loss was investigated. A forward and backward digit span test was applied to measure memory loss. Structural equation modeling (SEM) was established, and SPSS Amos was used for analysis. The results show a partial mediation effect of depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
3
16
0
1
Order By: Relevance
“…This finding confirmed our hypothesis: namely, that the older adults who used WeChat were at lower risk of depression, which, in turn, was beneficial in increasing their memory performance. This finding was consistent with previous studies [ 50 , 76 ]. For example, through an investigation of 3036 senior high school students in China, Sha and Dong analyzed the association between TikTok use and memory loss, and they found that depression partially mediated the relationship [ 50 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding confirmed our hypothesis: namely, that the older adults who used WeChat were at lower risk of depression, which, in turn, was beneficial in increasing their memory performance. This finding was consistent with previous studies [ 50 , 76 ]. For example, through an investigation of 3036 senior high school students in China, Sha and Dong analyzed the association between TikTok use and memory loss, and they found that depression partially mediated the relationship [ 50 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with previous studies [ 50 , 76 ]. For example, through an investigation of 3036 senior high school students in China, Sha and Dong analyzed the association between TikTok use and memory loss, and they found that depression partially mediated the relationship [ 50 ]. Through investigating older adults in China, this study adds new empirical evidence to the mediating effect of depression between social media use and memory performance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…With over 1 billion cumulative views, almost half of the assessed TikTok videos included in this study reported or expressed symptoms of mental distress. Other studies have observed the expression of mental ill-health within online social media platforms [ 31 ] and expressed concern about potentially traumatic and “triggering” TikTok videos as being detrimental to some viewers [ 32 ]. This is especially concerning given the frequency of screen time among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially concerning given the frequency of screen time among adolescents. Many adolescents are predominant TikTok participants, and there is a potential for contribution to poor mental health outcomes from repetitious and prolonged viewing, especially if traumatic events are featured in the videos [ 32 ]. Recently, TikTok has acknowledged the substantial impact of their platform on users’ mental health and have provided additional resources in support of user safety, health, and mental wellness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%